La cultura de guerra franquista como pauta de regulación conductual - Fernando Ampudia de Haro (Amnis)
The aim of this paper is to analyze the war culture that has been constructed and transmitted through handbooks of good manners and civism published during the franquist dictatorship. As I will sustain, war culture operates as an emotional and behavioral pattern, through which individuals would be socially integrated in a national community, sharing its values, beliefs and rules and establishing a radical difference from the emotional and behavioral patterns of those individuals, who had been vanquished.